Theoretical model of the aqua-copper [Cu(H2O)5]+ cation interactions with guanine - Burda, Jaroslav V; Shukla, Manoj K; Leszczynski, Jerzy (Journal of molecular modeling, 2005)
Pentaaqua complexes of Cu(I) with guanine were optimized at the DFT B3PW91/6-31G(d) level. For the most stable structures, vibration frequencies and NBO charges were computed followed by energy analyses. The order of individual conformers was very sensitive to the method and basis sets used for the calculation. Several conformers are practically degenerated in energy. The inclusion of an entropy term changes the order of the conformers' stability. Water molecules associated at the N9 position of guanine are favored by the inclusion of the entropy correction. Bonding energies of Cu-O(aqua) interactions were estimated to be about 60 kcal mol(-1) and for Cu-N7 bonding in the range of 75-83 kcal mol(-1). The broad range in Cu-N interaction energies demonstrates the role of induction effects caused by water molecules associated at the various sites of guanine. The charge distribution of the guanine molecule is changed remarkably by the coordination of a Cu(I) cation, which can also change the base-pairing pattern of the guanine.
Keywords: chemické modely; měď; molekulární struktura; Models, Chemical; voda; Thermodynamics; termodynamika; Copper; guanin; vodíková vazba; Guanine; Water; Molecular Structure; elektrony; Hydrogen Bonding; Electrons